2022
DOI: 10.1002/ecs2.4171
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic features mediate marine subsidies to island food webs

Abstract: Although marine subsidies often enrich terrestrial ecosystems, their influence is known to be context‐dependent. Additionally, the multitrophic impact of marine subsidies has not been traced through food webs across physically diverse islands. Here, we test predictions about how island characteristics can affect marine enrichment of food web constituents and how nutrients flow through island food webs. To evaluate enrichment and trace marine nutrients across food webs, we used stable isotopes of soil, flora, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
0
7
2
Order By: Relevance
“…Additionally, it remains unclear whether species richness decreases with increases in soil δ 15 N because plant species cannot tolerate disturbances caused by the subsidy source, or if C. nutkaensis is outcompeting other species on a local scale. Finally, despite previously finding higher wrack biomass corresponding to 15 N enrichment in two plant species on the same set of islands (Obrist et al, 2022), we found no evidence of wrack affecting patterns in plant species diversity at the plot scale nor at the island scale. Given the high productivity of kelp forests in the study area (Steneck et al, 2002;Wilmers et al, 2012), we initially thought that wrack would be one of the main contributions of marine inputs to the islands in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Additionally, it remains unclear whether species richness decreases with increases in soil δ 15 N because plant species cannot tolerate disturbances caused by the subsidy source, or if C. nutkaensis is outcompeting other species on a local scale. Finally, despite previously finding higher wrack biomass corresponding to 15 N enrichment in two plant species on the same set of islands (Obrist et al, 2022), we found no evidence of wrack affecting patterns in plant species diversity at the plot scale nor at the island scale. Given the high productivity of kelp forests in the study area (Steneck et al, 2002;Wilmers et al, 2012), we initially thought that wrack would be one of the main contributions of marine inputs to the islands in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, despite previously finding higher wrack biomass corresponding to 15 N enrichment in two plant species on the same set of islands (Obrist et al, 2022 ), we found no evidence of wrack affecting patterns in plant species diversity at the plot scale nor at the island scale. Given the high productivity of kelp forests in the study area (Steneck et al, 2002 ; Wilmers et al, 2012 ), we initially thought that wrack would be one of the main contributions of marine inputs to the islands in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Marine‐derived nitrogen is likely a good indicator of river otter activity on these islands. Their latrines create major onboarding spots for marine‐derived nutrients that can flow in many directions through different processes, impacting island food webs (Ben‐David et al, 1998; Obrist, Hanly, et al, 2022). In addition to creating hotspots of marine flow, river otter behaviour can also impact habitats through smaller, localized disturbances to coastal vegetation and soils.…”
Section: Discussionmentioning
confidence: 99%
“…fundamental ecological theory, such as the intersection between subsidies and Island Biogeography Theory (Anderson & Wait, 2001;Obrist et al, 2022).…”
mentioning
confidence: 99%